Correlation between the performance in the Special Judo Fitness Test and the Wingate Anaerobic Test - Antoni Szmuchrowski, L.; Andrade Rodrigues, S.; Fontes Corgosinho, R.; Souza Pinheiro, G.; Ferreira Pedrosa, G.; Motta Drummond, M. D.; Gonçalves, R.; Miranda Rohlfs, I.; Pena Couto, B. (Archives of Budo, 2013)
To characterise the energy demands of judo, researchers have verified the relevant contribution of anaerobic energy supply to athletes during fights. To evaluate anaerobic capacity, the Wingate Anaerobic Test (WAnT) was developed, which is based on the use of the lower and upper limbs. Sterkowicz created the Special Judo Fitness Test (SJFT), which consists of a repeated execution of the "ippon-seoi-nage". A comparison between the results of these tests allows a verification of the validity of the utilisation of WAnT as a predictor of specific performances in judo. The aim of this study was to correlate the results between WAnT and SJFT for the lower and upper limbs. Material and Methods: Seventeen professional Brazilian judo athletes (mean age 19.16 ± 2.06 yrs, mean body mass 88.24 ± 26.50 kg and mean height 1.76 ± 0.10 m) participated in the study. The athletes underwent both the SJFT and the WAnT for upper and lower limbs. Results: A significant correlation between the SJFT and WAnT results was not observed for the upper and lower limbs. There was a statistically significant correlation between the number of throws in the third set of SJFT (30"B) and the average power in WAnT for the upper limbs; however, the correlation was weak. Conclusions: Because of the lack of a significant correlation between the indicators of the SJFT, the WAnT most likely does not have enough specificity to make an adequate evaluation of the anaerobic capacity of judokas.